Cavitation inception from transverse waves in a thin liquid gap - Rapet, Julien (2020)
It is well known that dielectric breakdown in a liquid generates cavitation bubbles and shock waves. Here we demonstrate that when the liquid is bounded by two solid glass boundaries (10–20-μm separation), rings of microscopic bubbles can be nucleated around the laser-induced cavitation bubble. While generally acoustic nucleation is achieved with longitudinal waves of sufficient tension, this work demonstrates that acoustic cavitation can also be generated from transverse waves. Our experiments identify three waves originating at the boundaries: the fastest is the bulk wave in the solid, followed by a leaky Rayleigh wave at the liquid-solid contact, which is trailed by a Lamb-type wave. For the latter, the two solid boundaries act as a wave guide and generate intense and short-lived cavitation activity within the gap. Streak photography and high-speed photography reveal the microsecond-duration cavitation-bubble dynamics, and subpicosecond strobe photography visualizes the mechanism of bubble nucleation from the accelerated surface. Simulations coupling the solid mechanics with the acoustics support the experimentally observed mechanisms of transverse-wave-induced cavitation inception.